PENGABDIAN MASYARAKAT PEMBELAJARAN BUDAYA DI SMA KARANGPANDAN, KARANGANYAR PADA ERA DIGITAL - Sawitri, Sawitri; Nurpeni Priyatiningsih; Harsono, Harsono; Bambang Ikwanto (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
Community service in the form of cultural learning using digital technology represents a significant innovation in education, especially in the modern era where teaching methods must adapt to technological advancements. This program was implemented at SMA Karangpandan, Karanganyar, to address the issue of student disengagement and boredom with traditional, monotonous learning methods. The community service team, consisting of lecturers from various academic backgrounds such as culture, language, elementary education, and health, provided training and guidance to teachers to enhance their digital teaching skills. The program introduced various digital learning methods, including podcasts, online community-based learning, adaptive learning, e-learning platforms, webinars, augmented reality (AR), virtual reality (VR), and digital resources such as e-books. The results showed a significant improvement: prior to the program, only 20% of teachers utilized digital methods, but this increased to 75% after the intervention. The pre-test and post-test results demonstrated a marked increase in teachers’ abilities to integrate digital technology into their teaching. This community service initiative successfully contributed to the advancement of digital-based learning, making the educational process more engaging and relevant to the needs of today’s students.